INNOVATION ESSENCE AND SENSE OF CATEGORY “CIVILIZATION CHRONOTOPE” - O. Dombrovsky (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The problem of “civilizational chronotope” is revealed in the paper as the innovation category of modern economic theory and the next step in its evolution.